Gangguan Berbicara Cadel pada Aktor Junior Roberts: Kajian Psikolinguistik - Sari, Putri Aprilia; Afrilanda, Wa Adira (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
This research focuses on the speech disorder known as "cadel," experienced by Junior Roberts, an actor, through a psycholinguistic approach. The background of this study highlights the importance of understanding language disorders, particularly in everyday communication contexts. The identification of issues indicates that "cadel" can occur not only in children but also in teenagers and adults, leading to difficulties in pronouncing certain phonemes, such as /r/, which is often pronounced as /l/. The objective of this research is to analyze the patterns and mechanisms of phoneme changes occurring in individuals with "cadel" and to understand the meanings contained in their speech. The methodology employed is qualitative descriptive, with data collected through observation and transcription from the sketch show "Lapor Pak" on YouTube, yielding 10 relevant data points. The findings reveal that the phoneme changes observed in Junior Roberts include the pronunciation of words such as "barlang" becoming "barang" and "inggrlis" becoming "inggris." The discussion uncovers that variations in substituted phonemes can differ among individuals, influenced by psychological and environmental factors. Recommendations emphasize the need for greater attention to managing speech disorders like "cadel," along with the importance of support from the surrounding environment to enhance communication abilities, enabling better interaction within society. This research aims to provide deeper insights into the relationship between phonology and language psychology and encourages further studies in this field.